The Role of Nutrients in a Dietary Intervention in Improving Blood Cholesterol Profile and Lowering Cardiovascular Risk - Augusto Innocenti; Ferdinando Franzoni; Carlo Pruneti (Journal of Basic & Applied Sciences, 2021)
Low-density lipoprotein cholesterol has been positively associated to an increase of cardiovascular risk by a large number of epidemiological studies. On the contrary, high-density lipoprotein cholesterol results inversely related to cardiovascular risk. In this contest plasma total cholesterol and low-density lipoprotein cholesterol concentration, and the total cholesterol – high-density lipoprotein cholesterol ratio seems to be able to predict cardiovascular risk. Diet and its composition affects various plasma cholesterol concentration and their ratios. Particularly, a reduction of saturated fat acids dietary intake is strictly related to both improve of blood lipid profile and reduction of cardiovascular events incidence. On the other hand, the evidences from epidemiologic and clinical studies are consistent in finding that the reduction of cardiovascular risk depends by nutrients used for replacing saturated fat acids. Specifically it has been demonstrated that replacement of saturated fat acids with unsaturated fat acids, either monounsaturated or polyunsaturated ones, is effective in improving cardiovascular risk. On the contrary, saturated fat acids replacement with high glycemic index refined carbohydrate actually increases cardiovascular risk. Despite that, many dietary guidelines do not give any tips about nutrients to use in replacement of saturated fat acids, underestimating the significance. In this perspective Mediterranean diet, represents an attractive dietary pattern for the improvement of blood lipid profile and the reduction of the cardiovascular risk.